New Directions in Thomas Paine Studies - Cleary, Scott; Stabell, Ivy Linton; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book propels the study of American revolutionary and radical Thomas Paine into the twenty-first century by engaging an interdisciplinary and international group of scholars in an exploration of Paine's role in politics, literature, and the invention of the global.
Keywords: Science; Science; Science, general; Electronic books